Feasibility of an Off-Road Landstreamer - Dupuis, Christian; Dimech, J.; Kepic, Anton (EAGE, 2013)
A series of tests compared the performance of a geophone sensor with plate coupling to the ground versus the conventional spike coupling in sandy and hard-packed ground with uneven surfaces. The purpose of these tests were to see if weight and footprint of a self-levelling sensor, where the geophone self-rights under gravity, were critial for performance. The sensor is intended to operate off-road being twoed on a cable behind a vehcle as part of a landstreamer. Our tests indicate that these factors don't matter significantly. The plate sensor data match geophone data to better than 10% RMS difference in the 10-150 Hz band. Thus, using landstreamers with self-levellling geophones appears to be a robust approach to automating 2D surveys.